The Effect of Learning Habit and Learning Environment at School to The Students’ Achievement at Madrasah Tsanawiyah Insan Qur’ani Aceh Besar - Yulia Utami (Journal of International Conference Proceedings (JICP), 2020)
The title of this research was “the effect of learning habit and learning environment at school to the students’ achievement at Madrasah Tsanawiyah Insan Qur’ani Aceh Besar”, which aimed to know the effect of learning habit and learning environment at school to the students’ achievement both partially and simultaneously at Madrasah Tsanawiyah Insan Qur'ani Aceh Besar. The research used a quantitative approach with the kind of descriptive research. The population of research was the students in grade VIII that contain 128 students in the class and as the sample were 25 students. The sample was obtained by using Proportionate Stratified Random Sampling. The technique of collecting data will be obtained from observation, questionnaire, and documentation. The techniques of data analysis are used multiple linear regression analysis with t-test and f-test at a significant level of 0.05. The result of research showed that there was a significant effect of learning habit and learning environment to the students’ achievement.